2001
DOI: 10.1021/ie010173c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the SO2N-Formylmorpholine Complex:  Application to a Regenerative Process for Waste Gas Scrubbing

Abstract: This paper presents the results of fundamental investigations on physical and chemical interactions between sulfur dioxide and N-formylmorpholine (NFM), with a view to the development of a regenerative process for waste gas scrubbing. This solvent is a promising medium for such processes because of its high absorption capacity, its low-to-moderate vapor pressure for temperatures below 100 °C, and its reduced toxicity. The existence of a chemical interaction between SO2 and NFM, with the formation of a 1:1 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…[ 1 _ T D $ D I F F ] 6, it was also found that the stretching vibrational bands of carbonyl in DMF [26] shifts to lower frequency from (1676 to 1662) cm À1 , and stretching vibrational band of -[ 1 0 4 _ T D $ D I F F ] N-CH 3 in DMF [27] locates at 1256 cm À1 did not obviously change with the increasing DMF concentration. The stretching vibrational band of carbon hydrogen H-[ 1 0 5 _ T D $ D I F F ] C¼O in DMF shifts from (2858 to 2876) cm À1 [28][29][30][31]. The bending vibrational band of ether oxygen -[ 1 0 6 _ T D $ D I F F ] C-O-C-in DEG locates at 1128 cm À1 and 1059 cm À1 did not obviously change with the increasing DMF concentration.…”
Section: Spectral Measurementsmentioning
confidence: 99%
“…[ 1 _ T D $ D I F F ] 6, it was also found that the stretching vibrational bands of carbonyl in DMF [26] shifts to lower frequency from (1676 to 1662) cm À1 , and stretching vibrational band of -[ 1 0 4 _ T D $ D I F F ] N-CH 3 in DMF [27] locates at 1256 cm À1 did not obviously change with the increasing DMF concentration. The stretching vibrational band of carbon hydrogen H-[ 1 0 5 _ T D $ D I F F ] C¼O in DMF shifts from (2858 to 2876) cm À1 [28][29][30][31]. The bending vibrational band of ether oxygen -[ 1 0 6 _ T D $ D I F F ] C-O-C-in DEG locates at 1128 cm À1 and 1059 cm À1 did not obviously change with the increasing DMF concentration.…”
Section: Spectral Measurementsmentioning
confidence: 99%
“…Liquid temperatures were controlled at 308.15 K using the thermostatic bath (3) and registered on a standard thermometer (7) at different points, and the temperatures do not vary more than 0.02 K for about 30 min. Total pressures were recorded on pressure meter (8). SO 2 concentrations in gas phase were determined by GC (5) with FPD detector.…”
Section: Apparatusmentioning
confidence: 99%
“…There is considerable interest in the solubility of SO 2 because of its importance in industrial applications and in pollution control [1][2][3][4][5]. Among the many procedures employed to desulfurize exhaust gases, organic solvents used as absorbents have been identified as an option among the regenerative processes [6][7][8][9][10] because regeneration can be done by pressure reduction, by temperature increase, and by use of a carrier gas. Therefore, our research group has paid great attention to the (alcohol + water) system for SO 2 removal for several years [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As this process gives a large amount of solid waste cakes as by-products as well, the new absorption methods using organic solvents as SO 2 -removal agents have been explored because the absorbing agents can be regenerated repeatedly. [1][2][3][4][5] The SO 2 removal method by organic solvents is generally composed of two steps; 1) a fixation of SO 2 from the flue gas by the formation of a absorbent-SO 2 complex, and 2) thermal regeneration of absorbing agents and SO 2 stripping at the same time. The working process looks similar to that of an amine-CO 2 reaction which is an important CO 2 removal method from the flue gas.…”
mentioning
confidence: 99%
“…Only chemical engineers have been interested in this issue, and studied the SO 2 removal process experimentally. [1][2][3][4][5] In this regard we have conducted quantum mechanical computations to trace the reaction between amines and SO 2 , and to calculate binding energies of the stable Lewis acid-base complexes in both a gas phase and an aqueous environment. Lewis bases dealt with in this work were trimethylamine (TMA), triethylamine (TEA), monoethanolamine (MEA), pyridine, and methylpyrolidone (NMP), where NMP did not form an SO 2 complex via an N-S bond but reacts with SO 2 by forming a O(carbonyl)-S bond (Figure 1e).…”
mentioning
confidence: 99%